2022
DOI: 10.3390/su14159045
|View full text |Cite
|
Sign up to set email alerts
|

Food-Related Consumer Behavior Endorsing European Food Chain Sustainability—A Marketing Study on the Romanian Consumer

Abstract: The efforts of regulators and food industry actors to achieve ambitious European sustainability objectives should not only be based on, but also supported by, consumers’ behavior, since customers’ demand has the ability to determine changes in the whole food system. This paper’s systemic approach to customers’ sustainable food-related habits and opinions during purchase, consumption and waste management offers a comprehensive view of their decision criteria, their motivations and their preferred incentives. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For instance, Kodali et al (2013) found a positive impact of label elements (label design, nutritional information, health claims, accessibility, and quality). However, in Romania, consumers' distrust for sustainable labels and ecological products, and the European Union's food policy had a negative effect on consumption (Strambu-Dima, 2022). Unlike these results, labels appeared as neutral in case of Portuguese consumers.…”
Section: Introductionmentioning
confidence: 72%
“…For instance, Kodali et al (2013) found a positive impact of label elements (label design, nutritional information, health claims, accessibility, and quality). However, in Romania, consumers' distrust for sustainable labels and ecological products, and the European Union's food policy had a negative effect on consumption (Strambu-Dima, 2022). Unlike these results, labels appeared as neutral in case of Portuguese consumers.…”
Section: Introductionmentioning
confidence: 72%
“…In addition, in Romania, citizens generally might have doubts regarding sustainable products. For example, Romanian consumers have considered ecological products too expensive, and they have a lack of trust towards sustainable labels (Strambu-Dima, 2022). Furthermore, according to Orzan et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in Romania, citizens generally might have doubts regarding sustainable products. For example, Romanian consumers have considered ecological products too expensive, and they have a lack of trust towards sustainable labels (Strambu-Dima, 2022). Furthermore, according to Orzan et al (2018), a low consumer budget and deficiencies in the availability of information were considered the main barriers when adopting sustainable behaviour and buying products with sustainable packaging among Romanian consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Not without significance for building the resilience of supply chains are also dietary habits. Examining individuals' sustainable practices and perspectives throughout the stages of purchasing, consumption, and waste management provides a thorough understanding of their decision-making criteria, motivations, and preferred incentives (Strambu-Dima, 2022).…”
Section: Introductionmentioning
confidence: 99%